Kristjan Toomaspoeg. The Teutonic Order in Italy, 1100–1525: Building Bridges in the Medieval World. The Military Religious Orders: History, Sources, and Memory 11. London: Routledge, 2024. 216 pp. ISBN: 978-1-032-15347-6. - Rejner, Michał (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)